Accuracy of Iodine and Calcium Concentrations in Dual Energy Computed Tomography (DECT) (International Journal of Scientific Research in Science and Technology, 2024)
Objective: The purpose of this study was to assess accuracies of iodine and calcium concentrations in dual energy computed tomography (DECT). Method: This study was performed using an in-house phantom made from polyester resin. The in-house phantom had a diameter of 16 cm and had 10 holes filled with iodine (with concentrations of 5, 7.5, 10, and 15 mg/ml), calcium (with concentrations 200, 300, 500, and 600 mg/ml), water, and air. The in-house phantom was scanned by an Ultrafast kV Switching DECT (GE Revolution) with a tube voltage of 80/140 kV, rotation time of 0.5 s, and tube current variations of 200, 250, 300, 335, and 370 mA. Images was reconstructed to a material density image (MDI). The iodine and calcium concentrations were measured using GSI Viewer software and compared with set iodine and calcium concentrations. Results: It was found that absolute percentage error (APE) of concentrations on iodine was <12% and on calcium was <25% for all concentration variations. Hence, the APE of iodine is smaller than that of calcium. It was found that increasing the tube current does not necessarily improve the accuracy of iodine and calcium concentration measurements. Conclusion: Measurements of iodine and calcium concentrations have been carried out on DECT using an in-house phantom. Overall, iodine and calcium quantification in DECT using the in-house phantom is accurate.